2015
DOI: 10.1080/1023666x.2015.1054084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Treatment and Fiber Loading on Mechanical Properties ofBorassus(Toddy Palm) Fiber/Epoxy Composites

Abstract: The aim of the present study was to investigate and compare the mechanical properties of untreated and chemically modified Borassus fiber reinforced epoxy composites.Composites were prepared by hand lay-up process by reinforcing Borassus fibers with epoxy matrix. To improve the fiber-matrix adhesion properties, alkali (NaOH), and alkali combined with silane (3-aminopropyltriethoxysilane) treatments on the fibers surface were carried out. Examinations through Fourier transform infrared (FTIR) spectroscopy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…In this regard, François et al [38] reported a decrease in lignin content of hemp fibers up to 24.5% after scCO2 treatment. The spectral analysis revealed that the untreated flax fiber consists of alkene, esters, aromatics, ketone, and alcohol belonging to cellulose, hemicellulose, and lignin (Table 1), as already reported in [21,40]. Upon CO 2 supercritical treatment, slight shifts could be observed for the characteristic bands of flax.…”
Section: Characterization Of Flax Yarns After Scco 2 Treatmentsupporting
confidence: 77%
“…In this regard, François et al [38] reported a decrease in lignin content of hemp fibers up to 24.5% after scCO2 treatment. The spectral analysis revealed that the untreated flax fiber consists of alkene, esters, aromatics, ketone, and alcohol belonging to cellulose, hemicellulose, and lignin (Table 1), as already reported in [21,40]. Upon CO 2 supercritical treatment, slight shifts could be observed for the characteristic bands of flax.…”
Section: Characterization Of Flax Yarns After Scco 2 Treatmentsupporting
confidence: 77%
“…Compared to studies dealing with fruit fibre-reinforced thermoplastics, the strength values of 'Toddy palm y'/PLA and 'Toddy palm b'/PLA are on the level of toddy palm fruit fibre-reinforced high density polyethylene (HDPE) [15] and slightly above the values of fruit fibre-reinforced polycaprolactone (PCL) [16] while Young's moduli of toddy palm/PLA composites are significantly higher. Reddy et al [14] achieved higher values for fruit fibre-reinforced EP compared to our toddy palm/PLA composites. Since the 'Toddy palm y' and 'Toddy palm b' have significantly higher strength values than the fruit fibres investigated by Reddy et al [14] (compare Tab.…”
Section: Composite Characteristicsmentioning
confidence: 45%
“…Other examples are the studies of Srinivasababu et al [11] who investigated fibres from the leaflet in UP, Prabowo et al [12] and Rashid et al [13] who analysed ijuk fibre-reinforced polypropylene (PP) and phenolic composites, respectively. Reddy et al [14], Maheswari et al [15] and Sarasini et al [16] examined the characteristics of fruit fibre bundles in combination with EP, high-density polyethylene (HDPE) or polycaprolactone (PCL) for potential composite applications.…”
Section: Introductionmentioning
confidence: 99%
“…Figures (B), , (B), and (B) reveal that the modulus behavior does not show any clear trend with respect to fiber length and fiber load. Sometimes shortest fiber composites are most stiff, other times they are most compliant.…”
Section: Resultsmentioning
confidence: 93%
“…This has given an impetus to the research in the field of polymer composites and researchers are faced with the challenge of bringing out better composite materials. As a result, various natural fibers have been explored for reinforcing polymer matrices . The advantages of using natural fibers for reinforcement of polymers are easy availability, renewability, biodegradability, low density, high specific strength, noncorrosive nature, and low cost.…”
Section: Introductionmentioning
confidence: 99%